1994
DOI: 10.1093/jn/124.10.1950
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Citrulline but Not Ornithine Counteracts Dietary Arginine Deficiency in Rats by Increasing Splanchnic Release of Citrulline

Abstract: Ornithine and citrulline have different arginine-sparing capabilities when provided in an arginine-deficient diet. Rats were fed arginine-deficient diets containing ornithine or citrulline to see the effect on net fluxes of free arginine, ornithine and citrulline across the portal-drained viscera (PDV) and liver. The diets contained either 10 g arginine/kg diet (+Arg) or no arginine: the -Arg/+Ala diet contained additional alanine and the -Arg/+Orn and -Arg/+Cit diets contained ornithine and citrulline, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
31
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 27 publications
3
31
0
Order By: Relevance
“…As such, the majority of an oral Cit load passes into the systemic circulation, as reflected by a significant increase in plasma [Cit] after Cit ingestion in the current study and numerous previous reports (8,16,42,51,53). Thereafter, the bulk of plasma Cit is converted to Arg, mostly in the kidneys (15,24,59,65,70), but also in several other tissues (15,23,70). This is compatible with the significant increase in plasma [Arg] in this study and several previous studies (32,47,53,62) following Cit supplementation.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…As such, the majority of an oral Cit load passes into the systemic circulation, as reflected by a significant increase in plasma [Cit] after Cit ingestion in the current study and numerous previous reports (8,16,42,51,53). Thereafter, the bulk of plasma Cit is converted to Arg, mostly in the kidneys (15,24,59,65,70), but also in several other tissues (15,23,70). This is compatible with the significant increase in plasma [Arg] in this study and several previous studies (32,47,53,62) following Cit supplementation.…”
Section: Discussionsupporting
confidence: 77%
“…Cit is then extracted by the kidneys to be converted, in sequence, to argininosuccinate and Arg by the enzymes arginoinosuccinate synthase and arginoinosuccinate lyase, respectively (15,24,59,65,70). Synthesis of Arg from Cit is prevalent in other tissues (15,23,70), and this process is facilitated since Cit does not compete with ADMA for cell transport (50,69). Importantly, it has been shown that oral Cit supplementation more effectively increases the circulating (32,47,53,62) and tissue (63) [Arg] than an equivalent dose of Arg and that Cit supplementation can increase NOS activation (63) and NO biomarkers (46,53).…”
mentioning
confidence: 99%
“…Although urea cycle enzymes are abundant in the liver, hepatic release of arginine is low or absent in adult and growing rats (17,20,32), mice (19), and humans (3), even when fed an arginine-free diet (20,21). Adult mammalian hepatocytes have high arginase (EC 3.5.3.1) activity (15,16,22), and there is tight channeling of urea cycle between the cytoplasmic urea cycle enzymes (13), presumably resulting in efficient ammonia detoxification to urea.…”
Section: Discussionmentioning
confidence: 99%
“…Although arginine is synthesized by the liver and kidney, this amino acid, in a manner similar to dietary essential amino acids, shows a decreased concentration in plasma or blood if omitted from the diet of rats (Gross et al, 1991;Hartman and Prior, 1992;Hartman et al, 1994). An imbalanced pattern of essential amino acids in the diet produces an imbalanced pattern of amino acids in muscle tissue, characterized by an exaggerated decrease in the concentration of the most-limiting amino acid in the diet (Leung et al, 1968).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported Prior, 1992 and1996;Hartman et al, 1994) effects of four arginine-free diets on blood concentrations and organ fluxes of amino acids. When alanine, glutamate, ornithine or citrulline were individually substituted for arginine in the diet, concentration of the substituted amino acid was increased in the blood with the exception of glutamate.…”
Section: Introductionmentioning
confidence: 99%